Factors associated with depression among adolescents living with HIV in Malawi. Issue 1 (December 2015) - Kim, Maria; Mazenga, Alick; Yu, Xiaoying; Devandra, Akash; Nguyen, Chi; Ahmed, Saeed; Kazembe, Peter; Sharp, Carla
Abstract Background Prior research suggests that a high prevalence of depression, with a detrimental impact on treatment outcomes exists among HIV-infected youth. Data on potential risk factors of depression among HIV-infected youth in sub-Saharan Africa are scarce. This cross-sectional study aimed to identify contributory/protective factors associated with depression in Malawian adolescents 12–18 years old living with HIV. Methods Depression was measured by a validated Chichewa version of the Beck Depression Inventory version-II (BDI-II) and the Children's Depression Rating Scale-Revised (CDRS-R). Data on variables thought to potentially be contributory/protective were collected and included: socio-demographics, past traumatic events/stressors, behavioural factors/social support, and bio-clinical parameters. Chi-square test or two-samplet -test was used to explore associations between factors and depression. Additional testing via linear/logistic regression, adjusting for age and sex, identified candidate variables (p < 0.1). Final regression models included variables with significant main effects and interactions. Results Of the 562 participants enrolled (mean age, 14.5 years [SD 2.0]; 56.1 % female), the prevalence of depression was 18.9 %. In multivariate linear regression, the variables significantly associated with higher BDI-II score were female gender, fewer years of schooling, death in the family/household, failing a school term/class, having a boyfriend/girlfriend, not disclosed or not having shared one's HIV status with someone else, more severe immunosuppression, and bullied for taking medications. Bullying victimization was reported by 11.6 % of respondents. We found significant interactions: older participants with lower height-for-age z-scores and dissatisfied with their physical appearance had higher BDI-II scores. In multivariate logistic regression, factors significantly associated with depression were: older age, OR 1.23 (95 % CI 1.07-1.42); fewer years of schooling, OR 3.30 (95 % CI 1.54-7.05); and bullied for taking medications, (OR 4.20 (95 % CI 2.29-7.69). Conclusion Having fewer years of schooling and being bullied for taking medications were most clearly associated with depression. Programmes to support the mental health needs of HIV-infected adolescents that address issues such as disclosure, educational support, and, most notably, bullying may improve treatment outcomes and are recommended.